Respuestas
Respuesta dada por:
1
a) 27+√81÷3-(2+3)°+49÷7
27+9÷3-1+7
27+3-1+7
36.
b) (3²+5³)/2 +(3-2/2)
(9+125)/2 +(3-1)
134/2+2
67+2=69
27+9÷3-1+7
27+3-1+7
36.
b) (3²+5³)/2 +(3-2/2)
(9+125)/2 +(3-1)
134/2+2
67+2=69
Respuesta dada por:
0
Respuesta: a= 36 y b= 69.
Explicación paso a paso:
Así se realizan estas operaciones
a) 27+√81÷3-(2+3)°+49÷7
27+9÷3-1+7
27+3-1+7
36.
b) (3²+5³)/2 +(3-2/2)
(9+125)/2 +(3-1)
134/2+2
67+2=69
Preguntas similares
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años